Rilievo 3D e fotogrammetria digitale per lo studio e la valorizzazione dell’habitat rupestre: l’ipogeo sotto Sotto Castello e la Basilica di San Giovanni a Rometta (ME) - Patti, Daniela (Archeomatica, 2022)
The paper focuses on the basilica in Contrada S. Salvatore and the hypogeum in Contrada Sotto Castello of Rometta (Sicily). Investigating these sites is not an easy task, due to the difficulties in defining their typology and chronology. The archeological survey and the geometric representation of these complex shapes and highly irregular surfaces are actually challenging tasks. Considering the particular nature of these rock settlements, they have been investigated by means of ICT tools (tri-dimensional surveys, digital Photogrammetry), which prove to be useful not only for scientific research, but also for communication purposes and for the exploitation of cultural heritage.